The law of targeting - Boothby, William H. (Oxford University Press, 2012)
Comprehensively examining all aspects of the law of targeting in military operations, the book assesses controversies in the rules governing targeting, including the use of human shields, the level of care required in a bombing campaign, and in the determination of whether someone is directly participating in hostilities